Bio-based crotonic acid production route via direct pyrolysis of bacterial polyhydroxybutyrate inclusions - Zakaria @ Mamat, Mohd Rahimi (2015)
Crotonic acid is a short-chain unsaturated carboxylic acid which can be utilized in a wide variety of applications such as resins, polymers, drug-ligand agents, and insecticides. Its current industrial production is from non-renewable petrochemical resource, using hydrocarbon as starting material which is converted into ethylene and several chemical intermediates before obtaining crotonic acid as a product of oxidation of crotonaldehyde. The utilization of hydrocarbon has become a concern due to various environmental and economical issues such as pollution, limited availability and increasing price of the hydrocarbon. Therefore, alternative methods have to be developed to reduce dependence on hydrocarbon and ensure sustainable economy and environment. This study was aimed to develop a simple production method for bio-based crotonic acid via pyrolysis of bacterial polyhydroxybutyrate (PHB) inclusions. Bacterial biomass containing PHB was obtained via fermentation of sugar by PHB producing bacteria, Cupriavidus necator NCIMB 11599 at limited phosphate concentration. PHB biomass was subjected to dynamic and isothermal pyrolysis to evaluate thermal degradation behavior and to collect the pyrolyzate produced. The pyrolyzate was analyzed by gas chromatography - mass spectrometry (GC-MS) and proton nuclear magnetic resonance (1H-NMR) to determine its composition. It was found that PHB inclusions with 66±3 % PHB content had different thermo gravimetric (TG) profile compared to pure PHB. PHB inclusions exhibited multi-step degradation which was contributed by presence of PHB, water and bacterial cell components. PHB in the inclusions had temperature degradation range of 270 – 340 °C. Later, when PHB inclusion were pyrolyzed in glass tube oven at its maximum degradation temperature, it was found that the pyrolyzate consisted of 56.8 % monomer, 30.6 % dimer, 9.4 % trimer and 3.2 % impurities. Recovery yield of biocrotonic acid obtained in this study was ~63 %, which is approximately 30 % higher than the conventional petrochemical-based CA. Furthermore, the proposed method also has other advantages such as renewable raw materials with less and simple processing steps. Economic analysis also revealed that crotonic acid price from both proposed bio-based and petrochemical-based was comparable (USD 7.80 - 11.05 and USD 6.75 - 13.50 respectively). In addition, effects of pyrolysis parameters (temperature and retention time), pretreatment and catalyst were also studied in order to increase biocrotonic acid yield and to reduce the amount of impurities in the pyrolyzate. Results showed that no significant changes of biocrotonic acid yield for temperature range of 300 – 340 °C. Therefore, the temperature of maximum degradation rate of PHB was used for subsequent experiment. Meanwhile, retention time of 20 min showed highest biocrotonic acid recovery yield (66.25 %). Besides that, when the bacterial cells were pretreated by homogenization and combined homogenization with ethanol washing, biocrotonic acid recovery was further improved by 6 % and 8 %, respectively, indicating that improving PHB purity could reduce impurities content and increase the recovery yield. Meanwhile, addition of MgO and Mg(OH)2 as catalysts resulted in significant selective formation of biocrotonic acid. Catalyzed biocrotonic acid production using MgO and Mg(OH)2 yielded 64.07 % and 70.60 % biocrotonic acid with 96.10 % and 95.75% purity respectively. Overall, results obtained from this research showed that biocrotonic acid production from pyrolysis of bacterial inclusions could be a promising method for alternative industrial production of crotonic acid as it does not only provide renewable chemical, but also simpler in production method and yielded higher crotonic acid recovery.